The Cow's Milk-Related Symptom Score (CoMiSS™): A Useful Awareness Tool - Bajerova, Katerina; Salvatore, Silvia; Dupont, Christophe; Eigenmann, Philippe; Kuitunen, Mikael; Meyer, Rosan; Ribes-Koninckx, Carmen; Shamir, Raanan; Szajewska, Hania; Vandenplas, Yvan (Nutrients, 2022)
The Cow’s Milk-related Symptom Score (CoMiSS™) was developed as a clinical tool aimed at increasing the awareness of health care professionals for the presence and intensity of clinical manifestations possibly related to cow’s milk (CM) intake. This review summarizes current evidence on CoMiSS. We found twenty-five original studies, one pooled analysis of three studies, and two reviews on CoMiSS. Infants exhibiting symptoms possibly related to CM, present with a higher median CoMiSS (6 to 13; 16 studies) than apparently healthy infants (median from 3 to 4; and mean 3.6−4.7; 5 studies). In children with cow’s milk allergy (CMA), 11 studies found that a CoMiSS of ≥12 predicted a favorable response to a CM-free diet; however, sensitivity (20% to 77%) and specificity (54% to 92%) varied. The decrease of CoMiSS during a CM elimination diet was also predictive of a reaction to an oral food challenge to diagnose CMA. A low CoMiSS (<6) was predictive for the absence of CMA. It was shown that no special training is required to use the tool in a reliable way. Intra-rater reliability was high with very low variability (intra-class correlation 0.93; 95% confidence interval 0.90−0.96; p < 0.001) in repeated assessments. This review found that CoMiSS cannot be considered as a stand-alone CMA diagnostic tool, but that it is a useful awareness tool for CMA as well as for monitoring symptom improvement.
Keywords: mléko; Reproducibility of Results; reprodukovatelnost výsledků; food allergy; alergie na mléko; Allergens; cow’s milk; skot; alergeny; ženské pohlaví; infant; zvířata; Humans; Milk Hypersensitivity; Cattle; Milk; CoMiSS; cow’s milk allergy; Female; lidé; Animals